"Big dictionary" of Arabic Language Academy in Cairo as an alternative of Arabic Historical Dictionary of August Fisher (Journal of Oriental Studies, 2016)
The article narrates the first steps towards learning and scientific description of the dynamics of the vocabulary of the Arabic language, it affects the discussion questions of historical lexicography. For the first time in domestic Arabic studies provide information about the first Arabic historical dictionaries, their methods in the selection of sources, the location of the illustrative material, the advantages and disadvantages of the proposed methods.